Sustainable Strategic Management : Qualitative Case Study Research of Three Companies Operating in Malaysia - Goudarzi, Mona (2014)
From the holistic point of view, SSM is gaining considerable attention and it is becoming vital for companies to comply their business models to include the value creation for all stakeholders. Decades ago SSM were mostly seen in developed countries, perhaps as what Parnell et al (2010) referred to, it was due to the already established strong foundation which enabled developed countries and their firms to invest in this area. Nevertheless, SSM is gaining more power in developing countries and more attention is being paid in this region now. Developing countries such as Malaysia, due to their nature have their own unique social and environmental problems. For sustainable development and having granted future for both companies and communities, these problems need to be addressed by the firms which are operating in Malaysia. Therefore in this study, the effort was to focus on Malaysia as a representative of developing countries. Consequently three qualitative case studies have been shaped based on the firms which are operating in Malaysia and announcing that they are conducting SSM. The first aim of this research is to examine what they perceive as SSM, since SSM may mean different thing for different people. These companies have been further examined from the perspective of institutional pillars. Afterward, the study tried to identify the sources of financial value creation for these companies.